Who controls the Internet? : illusions of a borderless world - Goldsmith, Jack L. (Oxford University Press, 2006)
Will cyberanarchy rule the net? And if we do find a way to regulate our cyberlife, will national borders dissolve as the Internet becomes the first global state? In this provocative new work, Jack L. Goldsmith and Tim Wu dismiss the fashionable talk of both a "borderless" net and of a single governing "code." Territorial governments can and will, they contend, exercise significant control over all aspects of Internet communications. Examining policy puzzles from e-commerce to privacy, speech and pornography, intellectual property, and cybercrime, "Who Controls the Internet" demonstrates that individual governments, rather than private or global bodies, will play that dominant role in regulation. Accessible and controversial, this work is bound to stir comment